CHEMICAL COMPOSITION AND ANTIBACTERIAL ACTIVITY OF THE ESSENTIAL OIL OF THE Toona sureni (Blume) Merr - Ekaprasada, M. Taufik; Nurdin, Hazli; Ibrahim, Sanusi; -, Dachriyanus (Universitas Andalas, 2009)
ABSTRACT The essential oil composition of the Toona sureni (Blume) Merr leaf was analyzed by GC-MS. More than 68 peaks, representing 99.99% of total oil, forty three components were identified, this represents 80.65% of the total oil component. The major components were α-terpinene (9.58%), α-copaene (8.39%), bicyclogermacrene (7.61%), δ-cadinene (6.65%), β-elemene (4.88%), germacrene-D (4.65%), δ-selinene (3.58%), caralene (3.10%), β-caryophyllene (2.88%), α-cubebene (2.82%), δ-gurjunene (2.20%), and (-)-isoledene (2.05%). The antibacterial activity of the essential oil of Toona sureni (Blume) Merr leaf was evaluated using disk diffusion method. The oil was effective on the inactivation of Escherichia coli, Staphylococcus aureus and Bacillus subtilis. Keywords: Toona sureni (Blume) Merr, antibacterial activity, GC-MS, essential oil